Analisis higher order thinking skills (HOTS) siswa dalam menyelesaikan open ended problems matematika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Higher Order Thinking Skills..is an ability that is focused on thinking critically, creatively, deeperly and optimally. A process that develops thinking ability in the higher level than can be supported by giving open-ended problems. The given problems are open, asking students to think deeper to find multi solutions. It will direct students thinking to the higher level. This research aimed to analyze the students’ higher order thinking skills level on grade VII-A MTs PAB 1 Helvetia in finding solutions of open ended mathematics problems. This research oriented on qualitative which was presented descriptively. The researcher selected six students from grade VII-A MTs PAB 1 Helvetia as the research subject which were identified on the students’ higher order thinking skills level to find open-ended problems. The research data was obtained by giving the written test on open ended problems test to the students and also the interview. Based on the research, it was obtained that there were nine students were categorized HOTS in high level (26.47%), forteen students were categorized in middle level (41.18%) and eleven students were categorized in low level (32.35%).
Keywords: higher order thinking skills (HOTS); mathematic open ended problems